1998
DOI: 10.2166/wst.1998.0807
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized biofilms on granular activated carbon for removal and accumulation of heavy metals from contaminated streams

Abstract: Biofilms consisting of a matrix of exopolysaccharide and microorganisms developed over granular activated carbon (GAC) enhance metal uptake from solution several times more than that achieved by GAC alone. By specifically employing GAC, there is also the opportunity of developing biofilm/GAC systems that can both entrap metals and also adsorb, and ultimately degrade, polluting organic residues such as pesticides. Targets for this type of process could be dump site leachates, mine tailings and other industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…carboxylate, phosphate and amino groups) on the fungal cell walls. 38,39 The carboxylate and phosphate groups carry negative charges which allow the microbial cells to be potent scavengers of metal ions. 38,42 The experimental results are presented in Fig.…”
Section: Effect Of Ph On Biosorption Capacitymentioning
confidence: 99%
See 2 more Smart Citations
“…carboxylate, phosphate and amino groups) on the fungal cell walls. 38,39 The carboxylate and phosphate groups carry negative charges which allow the microbial cells to be potent scavengers of metal ions. 38,42 The experimental results are presented in Fig.…”
Section: Effect Of Ph On Biosorption Capacitymentioning
confidence: 99%
“…4 pH was increased from 4 to 7.4, but this seemed to level off very close to the fungal cell walls when the pH was greater than 7.4. 23,24,38,39 It should be noted that the metal ion-binding properties of an alginate are primarily determined by its monomeric composition and the length of the G-blocks. 40 The interaction of heavy metal ions with both Ca-alginate and immobilised fungus preparations could be primarily related to the carboxylate groups of the Ca-alginate and the cell wall components of the mycelia.…”
Section: Effect Of Ph On Biosorption Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures were suggested to control biofilm growth and to use bioindicators to predict total organic carbon (TOC) and COD removal efficiencies, using the observed strong positive correlation between the abundance of some protozoa in the liquid phase of the BAC bed and COD concentration in the effluent. Scott and Karanjkar (1998) presented studies showing the benefits and effects of a matrix of microorganisms developed on GAC in enhancing metal uptake and degradation from solution. The conditions under which the biofilm developed, including pH and temperature were studied in terms of subsequent influence on metal biosorption.…”
Section: Biological Granular Activated Carbonmentioning
confidence: 99%
“…Several studies have confirmed a strong microbial influence in passive remediation systems from both acidic and alkaline AMD (Bier, Voss, & Bernhardt, 2015;Jones et al, 2015;Senko, Wanjugi, Lucas, Bruns, & Burgos, 2008;Whitney, Tracey, & Jeanne, 2013). Bacteria can remove metals through adsorption to a surface, biosorption to biomass, immobilization, and precipitation, as has been successfully demonstrated in bioreactors (Chang, Hsu, Chiang, & Su, 2006;Diels et al, 1995;Scott & Karanjkar, 1998;Scott, Karanjkar, & Rowe, 1995;Travieso et al, 2002). They can also resolubilize metal precipitates, increasing soluble contaminant levels.…”
mentioning
confidence: 99%